Virtues of al-Farabi in the transformation of the city - Al-Yousif, Ibrahim Jawad; Kadhim, Mustafa Kamil Kadhim; Ameen, Sura Kassim Ameen (Iraqi Journal of Architecture and Planning, 2019)
The individual is the basis of the emergence of cities, through which the emergence of multiple cities differed in terms of location, history and population, but did not remain in the structure of the initial list until our present time without the transformation and change in the structure of the city and by its various functions such as housing and shopping and other services, whether the social aspect or Economic, political or religious, and therefore we find that the emergence of any architectural model in the city is linked to the individual and society through them are identified the nucleus of the first models and then changes to architectural models influenced by the changing social needs as a result of the spatial and temporal action of the era, Research problem "The role of the changing social needs that led to the transformation of the market model of the historic city of Baghdad." The aim of the research was to "demonstrate the impact of the social needs of the individual on the transformation of the pattern of basic formations in architectural models (markets) in the historic city of Baghdad." The research was based on an inductive analytical approach to a common reading between the virtues of al-Farabi and Maslow’s hierarchy of needs. It was based on the stages of the emergence of models of the traditional markets of Baghdad as a case study through which the vocabulary of the theoretical framework is applied in order to study the extent of the individual’s interaction with the changing social variables spatially and temporally, and the reflection on the individual’s profession in the city and its practice through the professional ethics of the work that is embodied in the city market.